Study of native extracts from raw lupin yellow and alfalfa yellow (like-sickle or romanian) by chromato mass spectrometry - Grechana, O. V.; Serbin, A. G.; Гречана, Олена Володимирівна; Сербін, А. Г.; Гречаная, Е. В.; Сербин, А. Г. (My University, 2018)
We have not found enough the scientific pharmacognostic works study Lucerne and Lupine that belong to the legume family (Fabaceae L.) despite wide dissemination and use them. That's why we studied by comparative and pharmacognosy representatives the common herbs from the Ukrainian flora. We have conducted a comparative analysis of the chemical composition and quantitative content of coumarins and other biologically active substances of primary and secondary biosynthesis in native extracts from the above-ground parts of the family Fabaceae L. - L. luteus L. and M. falcata L. subsp. romanica (Prodan) O. Schwähr & Klink. by gas chromatography-mass spectroscopy method. It identified 22 and 38 components, respectively. A complex of biologically active compounds includes higher hydrocarbons, terpenoids, fatty acids etc. Among them – derivatives of 4 oxycoumarin: 0.20% coumarin in the raw material of Lupinus luteus L.; there are dihydrocoumarin 1.60% and 13.13% in the raw material of grass Medicago falcata L. subsp. romanica (Prodan) O. Schwarz & Klink. Проведено порівняльне фармакогностичне вивчення двох представників родини бобових флори України з використанням методу газової хромато-мас-спектрометрії при аналізі нативного екстракту сировини люпину жовтого та люцерни жовтої. Ідентифіковано 22 та 38 компонентів відповідно. Біологічно активні сполуки включають вищі вуглеводні, терпеноїди, жирні кислоти, похідні 4-оксикумарину тощо. У сировині трави Lupinusluteus L. вміст кумарину склав 0.20%, у сировині трави Medicago falcata L. subsp. romanica (Prodan) O. Schwarz & Klink. було знайдено дигідрокумарину – 1.60 % та кумарину – 13.13 %. Проведено сравнительное фармакогностическое исследование двух представите лей сімейства бобовых флоры Украины с использованием метода газовой хромато-масс-спектрометрии при анализе нативного экстракта сырья люпина желтого и люцерны желтой. Идентифицированы 22 и 38 компонентов соответственно. Биологически активные соединения включают высшие углеводороды, терпеноиды, жирные кислоты, производные 4 оксикумарина и др. В сырье травы Lupinus luteus L. обнаружено кумарина 0.20%, дигидрокумарина в сырье травы Medicago falcata L. subsp. romanica (Prodan) O. Schwarz & Klink. найдено – 1.60 %, кумарина – 13.13 %.
Вивчення нативних екстрактів сировини люпину жовтого та люцерни жовтої (серпоподібної або румунської) методом хроматомас-спектрометрії
Изучение нативных экстрактов сырья люпина желтого и люцерны желтой (серповидной или румынской) методом хромато-масс спектрометрии
Keywords: Gas Chromatography-Mass Spectroscopy; Сoumarins; Phytochemistry Analysis; Fabaceae; Lupinus; Medicago; хромато-мас-спектрометрія; кумарини; фітохімічний аналіз; бобові; люпин; люцерна; хромато-масс-спектрометрия; кумарины; фитохимический анализ; бобовые; люпин; люцерна